Research of the CVT Efficiency Improvement based on Servo Motor Drive and Sliding Control - Meng Xianglei (Jixie chuandong)
Taking the Jatco CK2 transmission which is manufactured by Jatco company as the research object,through the research of CVT power loss,the transmission loss with reference to the largest proportion and how they are dependent on the drive and control performance are analyzed,and these contributions are loss of hydraulic pump drive power,clamping force and overload transmission slip. Based on the analysis,the measure of improvement drive and control is puts forward. When the servo motor driving system and transmission slip control is instead of hydraulic pump,the increased efficiency can be predicted,in 25% of the rated load,the CVT loss in half,and in full,it can be predicted the efficiency reduced by 25%.